Analisis Tingkat Pemahaman KPR Syariah pada Bank Syariah di Indonesia: Studi Pendahuluan - Mohamad Heykal (Bina Nusantara University, 2014)
Sharia banking has been growing in many countries since the birth of post-neo revivalist movement in the mid-20th century. The development of Indonesian sharia banking began with a workshop related with interests and banking held by MUI in Cisarua on 18th to 20th of August 1990. Since 1992 to 2013 it has been established 11 sharia commercial banks and 24 sharia conventional banks that open sharia business units and 156 Islamic Financing Bank. In terms of existing office, Islamic banks in Indonesia have reached 1737 bank offices and also Islamic bank units. Moreover, the market share of Islamic banking has almost reached 5% of the total market share banking in Indonesia. Islamic banking also has a mortgage product that is essentially different from the existing mortgage in the conventional banking. It is expected that the Islamic mortgage product will result a profit. The product is a product released for customers who require financing from Islamicbank to have a house. This early study used literature review method and secondary data. This study built an analysis of the mortgage program issued by Islamic banks in Indonesia. Research concludes that the notion of Islamic banking on mortgage product, especially Islamic financing mortgage, from the internal party has not well distributed yet.